Michał Wyrostkiewicz, Human Ecology. An Outline of the Concept and the Relationship Between Man and Nature, Lublin: Wydawnictwo KUL 2013. - Krauze, Łukasz (Teologia i Moralność, 2016)
RECENZJA: Michał Wyrostkiewicz, Human Ecology. An Outline of the Concept and the Relationship Between Man and Nature, Lublin: Wydawnictwo KUL 2013, ss. 128, ISBN 978-83-7702-846-9.